2019
DOI: 10.1088/1361-6595/ab024f
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the voltage waveform’s shape and on-time duration on the dissolved ozone produced by a DBD bubble reactor

Abstract: In this study we examine both the effect of changing the applied voltage waveform shape and the modulation on-time on the amount of ozone dissolved within a liquid in a DBD bubble reactor. In this device, the discharge forms at the gas liquid interface allowing for effective transfer of the plasma effluent into the liquid. To produce different voltage waveforms, a multilevel inverter power supply capable of generating arbitrary waveforms without switching-on and switching-off transients has been used. Of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 35 publications
2
3
0
Order By: Relevance
“…Use of all the methods above, applied to an air plasma reaction set from [20], suggests that an optimal electron energy regime for ozone formation is a high amount of electron energy in the initial phase, and then no electron energy for the successive phases. This corresponds with evidence in the literature [10,24]. Use of the above methods also suggests that ozone destruction reactions occur much more rapidly at high electron energies, and at high temperatures (Fig.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Use of all the methods above, applied to an air plasma reaction set from [20], suggests that an optimal electron energy regime for ozone formation is a high amount of electron energy in the initial phase, and then no electron energy for the successive phases. This corresponds with evidence in the literature [10,24]. Use of the above methods also suggests that ozone destruction reactions occur much more rapidly at high electron energies, and at high temperatures (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…In addition to the simulated results shown above, the energy level regime predicted by the O 3 targeted run of OCARINA also agrees with a recent study by Seri et al [24] of the effect of different waveforms on ozone generation. The study observed that the best efficacy of energy input for ozone generation was achieved with relatively large spaces between on times to prevent ozone destruction reactions from occurring.…”
Section: Agreement With Literature Valuessupporting
confidence: 90%
“…Corona discharges [158,159], Dielectric Barrier Discharges (DBDs) [160,161] and gliding arcs [162,163] are most common plasma typologies utilized. On the other hand, bubbling reactors flush air bubbles within the water, and the plasma is ignited within these bubbles or onto the separation surface waterbubble [164,165]. This configuration usually enhances exchange surface between air and water, maximizing the amount of charges and reactive species diluted within the liquid.…”
Section: Discharge In Contact With Watermentioning
confidence: 99%
“…While a large number of RNS and ozone can be measured, some species such as H2O2, HNO2 and NO3 fell below the detection limit of FTIR or had overlapping peaks with other species; therefore the concentrations of those species were estimated from the computational results of Sakiyama et al, 2012. Concentrations of the reactive species achieved with a 30% duty cycle were then converted into partial pressures using the ideal gas law (see Table 2). Whilst a broad range of ROS and RNS species can be produced in atmospheric plasmas, the ratio between the two categories of species can be manipulated by changing the on-time and the duty cycle of the modulation (Ma et al, 2016;Seri et al, 2019). Lower duty cycles result in lower device temperatures, which is preferable for ozone production and minimisation of RNS production.…”
Section: Species Concentrations In the Plasma Effluentmentioning
confidence: 99%